1933 Haw. Sess. Laws 37-38, An Act Regulating the Sale, Transfer, and Possession of Firearms and Ammunition, § 4 - (:unkn) unknown (General Publisher, 1933)
Prohibited any person who resides in or is temporarily doing business within the Hawaiian territory from taking possesion of any firearm or ammunition, until after obtaining a permit allowing the possession of said items. Permits shall be issued by the chief of police of Honolulu or the sheriff of the county other than Honolulu. Permits to acquire rifles, pistols, revolvers, are limited to US citizens and accredited foreign officials aged twenty or more. Permits to acquite shotguns shall be given to individuals aged sixteen or more.
--
Keywords: POSSESSION